Two degrees up—Part One: Colombia - Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2010)
Small coffee producers in Colombia are already feeling the effects of climate change on this vital, high-value cash crop. At higher elevations in the southwestern Cauca department, production is still profitable, but as you move downhill you see the effect of what a two-degree temperature rise - projected for 2050 - could mean for the future of coffee production: devastated crops, and coffee farmers who have abandoned their coffee plants and been forced to move into less profitable crops. The farmers featured here, in Two Degrees Up: COLOMBIA, provide precisely the kind of testimonies that will help policymakers meeting in Cancun, Mexico for the COP16 Climate Change talks, need to hear.